Karakteristik Fisik, Kimia, Fungsional, dan Sensori Nasi Gurih Instan Dibandingkan dengan Nasi Putih Instan - Wardhani, Ajeng Widyaningrum Kusuma; Muhandri, Tjahja; Faridah, Didah Nur; Andarwulan, Nuri (Jurnal Teknologi dan Industri Pangan, 2024)
Variations of processing rice into cooked rice had long been developed. One of the rice products that had been widely circulated in the community was savory rice. Savory rice with an instantization processed was more practical in serving. This research aimed to determine the physical, chemical, functional, and sensory characteristics of instant savory rice compared to instant white rice. The stages of processing instant savory rice included washing, soaking, cooking, freezing, and drying. The freezing process was carried out at -20 °C for 24 h. The drying process for instant savory rice used a fluidized bed dryer for 3 h. Instant white rice was used as a control. The porosity level of instant savory rice was lower than instant white rice as indicated by the yield (95.77%), bulk density (0.57 g/mL), rehydration time (14.34 min), rehydration ratio (2.86), expansion volume ratio (2.26), and water absorption capacity (69.50%). Instant savory rice contained moisture content (8.48%), ash content (3.93%), fat content (5.56%), protein content (7.54%), and starch digestibility (54.84%) which was higher than instant white rice. Instant savory rice had carbohydrate content (82.97%), amylose content (32.39%), amylopectin content (46.59%), starch content (79.98%), and resistant starch content (1.90%) lower than instant white rice. In terms of sensory test results revealed that instant savory rice after rehydration was preferred by consumers compared to instant white rice regarding color, aroma, taste, texture, and overall with a score of 5.39-5.84.